2019 IEEE International Conference on Image Processing (ICIP) 2019
DOI: 10.1109/icip.2019.8803298
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Quality Assessment of 3d Point Clouds

Abstract: The real-world applications of 3D point clouds have been growing rapidly in recent years, but not much effective work has been dedicated to perceptual quality assessment of colored 3D point clouds. In this work, we first build a large 3D point cloud database for subjective and objective quality assessment of point clouds. We construct 20 high quality, realistic, and omni-directional point clouds of diverse contents. We then apply downsampling, Gaussian noise, and three types of compression algorithms to create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 58 publications
1
48
0
Order By: Relevance
“…This difference may be due to the fact that we consider only an asymmetric distance (from R to D). However, despite its good results on this dataset, the pure geometric distance has shown to behave very poorly in other datasets (e.g., [24]- [26]).…”
Section: ) Linear Model Optimizationmentioning
confidence: 75%
See 3 more Smart Citations
“…This difference may be due to the fact that we consider only an asymmetric distance (from R to D). However, despite its good results on this dataset, the pure geometric distance has shown to behave very poorly in other datasets (e.g., [24]- [26]).…”
Section: ) Linear Model Optimizationmentioning
confidence: 75%
“…one single type of degradation, such as in [23]). However, they report bad results for most of subjective datasets [24]- [26]. Very recently, Alexiou et al [25] proposed a metric based on differences of normal orientations and Meynet et al [6] proposed a metric integrating the curvature information.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For computable metrics of compressed PCs, similar to [7], [8], simple point-to-point and point-to-plane FR objective metrics, such as RMS and HD, showed no correlation with perceptual quality [9]- [12]. The conclusion that pointto-point and point-to-plane metrics are limited in predicting subjective quality ratings especially for TMC2 was also verified in [49], [50]. In [12], point-to-point and point-to-plane metrics were studied for a PC de-noising algorithm; they concluded that the point-to-plane metric is more correlated with perceptual quality than is a point-to-point metric for PC with no noise.…”
Section: B 3d Content Quality Assessmentmentioning
confidence: 82%